Audiology and communication disorders : an overview - Humes, Larry E.; Bess, Fred H. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
Using the innovative communication chain model that makes concepts and principles easy-to-understand, this 2nd edition covers structure and function of the auditory system; auditory disorders; audiologic measurement; screening for hearing loss and middle ear status; prosthetic devices for the hearing impaired; and rehabilitation and habilitation for individuals with impaired hearing. Boxed learning activities, case study vignettes, and commentaries help you understand audiology concepts and their clinical applications.Enhance your retention of key concepts with Learning Objectives, Key Terms, and Review Questions that build your understanding and challenge you to apply your knowledge.
Preceded by Audiology & communication disorders / Larry E. Humes, Fred H. Bess. 2008.
This book includes online access at http : //thepoint.lww.com/active, please refer library staff for the password
Includes bibliographical references and index.
Keywords: Communication Disorders; Hearing -- physiology; Hearing Disorders; Persons With Hearing Impairments -- rehabilitation; Audiology; Communicative disorders; Hearing; Hearing disorders